Medical online (non)professionalism: ethical and social risks of communication in digital media - S.I. Boyarkina (Векторы благополучия: экономика и социум)
In the context of rapid growth in the number of digital media and their audiences, the risks of online communication in medical practice represent a global problem: in highly digitalized countries, media become a public arena where discourses about the professionalism of medical workers are constructed, models for perceiving healthcare system issues are formed, and the terms of the social contract between society and representatives of the medical profession are debated. Aim. Based on the analysis of constructing social representations of physician competence in digital media, to identify criteria for evaluating competence and to outline the ethical and social consequences of mistakes in medical online communication. Methods. Using case study, narrative analysis, and content analysis methods, the study examines digital media print materials and user comments on Telegram and VKontakte regarding a regional case involving the mediatization of a doctor’s private video. The paper describes the components of the narrative constructed during online communication between media and users, and identified the main leitmotifs of the discourse in which the understanding of physician professionalism is formed. At the first stage, analysis of digital media materials (N=19) builds a narrative model jointly formed by authors and audiences. At the second stage, thematic content analysis of social network group user comments (N=863) identifies the main directions of discussion about the person and the doctor’s online communications. The study reveals the social foundations for assessing physician competence, its components, the conditions for its formation and control, and the context in which it is realized. The conclusion is that the understanding of online professionalism is jointly constructed by formal and informal actors involved in online communication, and includes clinical, moral‐ethical, and sociocultural components, which degree of development is linked to personal characteristics – age, work experience, and verbal and visual communication skills. The broad range of components included in the assessment also expands the list of institutional actors held responsible for violations of communication ethics.